2004
DOI: 10.1161/01.atv.0000131783.74034.97
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Findings of Coronary Atherosclerotic Plaques in Diabetics

Abstract: Objective-Coronary atherosclerotic plaque composition of diabetic subjects and localization of receptor for advanced glycation end products (RAGE) and its ligands have not been extensively studied. Method and Results-Hearts from diabetic subjects and age, race, and sex-matched nondiabetic subjects dying suddenly were examined. Coronary arteries were dissected and lesions were evaluated for plaque burden, necrotic core size, and inflammatory infiltrate. The expression of RAGE, the RAGE-binding protein (S100-A12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
344
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 473 publications
(376 citation statements)
references
References 40 publications
26
344
0
6
Order By: Relevance
“…OCT is the only intracoronary imaging modality that is capable of visualizing features of plaque vulnerability such as macrophage accumulation and TCFA that has been validated by histology studies 24, 25. Our results demonstrated that patients with DM had a higher prevalence of lipid‐rich plaque and macrophage accumulation at the culprit plaques, indicating a higher level of culprit plaque instability, consistent with previous pathology studies 18, 19…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…OCT is the only intracoronary imaging modality that is capable of visualizing features of plaque vulnerability such as macrophage accumulation and TCFA that has been validated by histology studies 24, 25. Our results demonstrated that patients with DM had a higher prevalence of lipid‐rich plaque and macrophage accumulation at the culprit plaques, indicating a higher level of culprit plaque instability, consistent with previous pathology studies 18, 19…”
Section: Discussionsupporting
confidence: 89%
“…Patients with DM have greater necrotic cores and increased levels of inflammation characterized as macrophages and T lymphocytes on pathology studies 18, 19. Moreover, poorly controlled DM is associated with a greater lipid burden 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and compared these with age-and sex-matched nondiabetics dying suddenly from coronary artery atherosclerotic disease (8). The basis for inclusion into the registry of sudden coronary death included either presence of an acute coronary thrombus or severe coronary atherosclerosis (one or more epicardial arteries with 75% or more cross-sectional luminal narrowing) and the absence of noncoronary causes of death at autopsy or prior surgery.…”
Section: Morphological Findings From the Registry Of Sudden Coronary mentioning
confidence: 99%
“…The interactions between S100 Ca 2+ -modulated proteins and RAGE receptors in the fine regulation of leukocyte trafficking and proliferation has been reviewed (21), but the role of EN-RAGE in atherosclerosis-related inflammation has not been studied. We applied immunohistochemical antibodies against RAGE and EN-RAGE (S100 A12) to coronary plaques of diabetics and nondiabetics (8). Although RAGE was found localized to macrophages, smooth muscle cells and endothelial cells, in both diabetics and nondiabetics, the overall expression of RAGE, as graded semiquantitatively, was significantly greater in diabetics (16.8±6.2 for diabetics and 10.0±6.1 for nondiabetics; P=0.004).…”
Section: Inflammatory Infiltrate In Diabeticsmentioning
confidence: 99%